Effects of blood storage age on immune, coagulation, and nitric oxide parameters in transfused patients undergoing cardiac surgery. Issue 4 (5th March 2019) - Spinella, Philip C.; Sniecinski, Roman M.; Trachtenberg, Felicia; Inglis, Heather C.; Ranganathan, Gayatri; Heitman, John W.; Szlam, Fania; Danesh, Ali; Stone, Mars; Keating, Sheila M.; Levy, Jerrold H.; Assmann, Susan F.; et al.
Abstract : BACKGROUND: Retrospective studies suggested that storage age of RBCs is associated with inflammation and thromboembolism. The Red Cell Storage Duration Study (RECESS) trial randomized subjects undergoing complex cardiac surgery to receive RBCs stored for shorter versus longer periods, and no difference was seen in the primary outcome of change in multiple organ dysfunction score. STUDY DESIGN AND METHODS: In the current study, 90 subjects from the RECESS trial were studied intensively using a range of hemostasis, immunologic, and nitric oxide parameters. Samples were collected before transfusion and on Days 2, 6, 28, and 180 after transfusion. RESULTS: Of 71 parameters tested, only 4 showed a significant difference after transfusion between study arms: CD8+ T‐cell interferon‐γ secretion and the concentration of extracellular vesicles bearing the B‐cell marker CD19 were higher, and plasma endothelial growth factor levels were lower in recipients of fresh versus aged RBCs. Plasma interleukin‐6 was higher at Day 2 and lower at Days 6 and 28 in recipients of fresh versus aged RBCs. Multiple parameters showed significant modulation after surgery and transfusion. Most analytes that changed after surgery did not differ based on transfusion status. Several extracellular vesicle markers, including two associated with platelets (CD41a and CD62P), decreased in transfused patients more than in those who underwent surgery without transfusion. CONCLUSIONS: Transfusion of fresh versus aged RBCs does not result in substantial changes in hemostasis, immune, or nitric oxide parameters. It is possible that transfusion modulates the level of platelet‐derived extracellular vesicles, which will require study of patients randomly assigned to receipt of transfusion to define.